Gestational syphilis in Sergipe: epidemiological factors and incidence from 2018 to 2021 (Research, Society and Development, 2023)
Infections concomitant with pregnancy can cause permanent damage to my mother and child. The Brazilian health system considers the severity of the attack by the main infections and calls for a prenatal care that tracks and identifies those that cause morbidity and mortality for the parturient and her child. Gestational syphilis is a bacterial disease with a high prevalence in the country, which can cause malformations and is a risk of transmission to the child during all phases of pregnancy. For this reason, it enters the Sistema de Informação de Agravos de Notificação (SINAN), in order to trace the epidemiological situation of each state regarding the incidence of cases and promote better prevention and treatment strategies. Despite the alarming picture, Syphilis is easily diagnosed and can be adequately managed to avoid negative effects. The present study aims to analyze the epidemiological characteristics of two cases of Gestational Syphilis notified and registered by the DataSUS platform in Sergipe in the period from 2018 to 2021, with the objective of correlating the information, determining a susceptibility profile and directing the increase in health care in this area.